Ecopathology: the influence of environment on disease - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Ecopathology is the study of the biological, physical, human and economic elements which may be causal factors of disease in livestock. There are some illnesses which, although not fatal, reduce productivity. In developing countries pastoralists...